A study on the effectiveness of Plusliner promotional strategies as an intercity bus service for Kuala Lumpur - Johor Bahru route / Suhaila Abdul Hanan - Abdul Hanan, Suhaila (1998)
Promotion plays an important role in market the new or existing product or service. As one of the marketing strategies, it helps in introducing and persuading people to use the product or service. In service industry such as transportation, promotion activities being carried out to introduce new service that is offered by the company. Park May Bhd. one of the public transport consortium has introduced express bus service called Plusliner. This thesis will discuss about the effectiveness of the promotional strategies that have been carried out to introduced the service. Focusing on Kuala Lumpur-Johor Bahru route, the rationale of the study is the route facing loading factor below expectation even after almost 6 month in operation. Besides that Plusliner also has to compete with the a number of existing competitors compare with Kuala Lumpur-Bukit Kayu Hitam and Johor Bahru-Bukit Kayu Hitam routes. All the competitors have different style of promotion in order to gain customer loyalty. Several problems have been identified to be the factors that may influence the loading factor. Lack of commitment from Park May's management to promotion activities, problem of using agent, improper ticket counter, high competition and unclear advertising and promotion objectives. In relation with it, research has been carried out to examine the problems in detail. The management fear to commit when the promotion cost is high.